MODEL MATEMATIKA PEMANASAN GLOBAL PADA KEHIDUPAN PESISIR - Farhan, Muhammad Miftah; Subhan, Muhammad (LPPM Universitas Bina Bangsa, 2024)
Global warming has become one of the big problems being faced in the 21st century. Global warming and depletion of the ozone layer due to excessive increases in Green House Gas (GHG) emissions in the atmosphere have a negative impact on the sustainability of coastal ecosystems. This research aims to describe the impact of rapid GHG emissions on coastal life, and this research also wants to determine the mathematical relationship between increasing GHGs and global warming. Rapid GHG emissions from various sources also drive global warming and cause several natural disasters. The method used in this research is the descriptive method. This research develops a mathematical model using four variables. Based on the results of simulation analysis, it shows that GHG and global warming can be controlled by ehriching coastal forests, but if not, the human population could lose the ability to survive and around one third of the total forest ecosystem will be lost by the end of this century